1999
DOI: 10.1006/dbio.1998.9107
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Matrix Metalloproteinases 2 and 9 in Regenerating Skeletal Muscle: A Study in Experimentally Injured andmdxMuscles

Abstract: Matrix metalloproteinases (MMPs) cooperatively degrade all components of the extracellular matrix (ECM). Remodeling of ECM during skeletal muscle degeneration and regeneration suggests a tight regulation of matrix-degrading activity during muscle regeneration. In this study, we investigated the expression of MMP-2 and MMP-9, in normal muscles and their regulation during regeneration process. We further investigated their secretion by C2C12 myogenic cell line. Two models of muscle degeneration-regeneration were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
288
3
10

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 282 publications
(332 citation statements)
references
References 58 publications
27
288
3
10
Order By: Relevance
“…For instance, work suggests MMP-9 is involved in mouse muscle regeneration by activating satellite cells (Kherif et al, 1999). Miyazaki et al (1996) found that Ntmmp-9 expression is up-regulated during newt limb regeneration.…”
Section: Role Of Mmps In Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, work suggests MMP-9 is involved in mouse muscle regeneration by activating satellite cells (Kherif et al, 1999). Miyazaki et al (1996) found that Ntmmp-9 expression is up-regulated during newt limb regeneration.…”
Section: Role Of Mmps In Regenerationmentioning
confidence: 99%
“…A number of MMPs found to be expressed during amphibian development, appear to be involved in the radical remodeling and cell death that occurs during amphibian metamorphosis, such as the loss of the larval tail and transformation of the intestine (Gross and Lapiere, 1962;Wang and Brown, 1993;Oofusa et al, 1994;Patterton et al, 1995;Brown et al, 1996;Ishizuya-Oka et al, 1996). MMPs are also thought to play a role in the process of regeneration in different systems (Yang and Bryant, 1994;Miyazaki et al, 1996;Kherif et al, 1999;Yang., 1999). For instance, in axolotls MMP-9 is upregulated after limb amputation and is thought to play a role in limb regeneration (Yang and Bryant, 1994;Yang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…27,64,65 MMP activity increases after muscle damage, 66,67 and satellite cells have been recognized as muscle cells that express MMPs on activation. 68 Increased MMP production results in efficient migration of satellite cells into injured areas. 66,68 Up-regulated Notch1 and STAT3 signaling may contribute to improved proliferation capacity and multipotency of SASCs from injured muscle because both Notch1 and STAT3 are involved in stem cell maintenance and self-renewal.…”
Section: Discussionmentioning
confidence: 99%
“…68 Increased MMP production results in efficient migration of satellite cells into injured areas. 66,68 Up-regulated Notch1 and STAT3 signaling may contribute to improved proliferation capacity and multipotency of SASCs from injured muscle because both Notch1 and STAT3 are involved in stem cell maintenance and self-renewal. 54,55,58,69,70 Activation of Notch1 and STAT3 signaling pathways is also required for efficient muscle regeneration, 51,57 and their activation in SASCs from injured muscle may verify the highly regenerative potential and important function of this specific cell population in repairing injured muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation